The Influence of the Application of Discovery Learning and Problem Based Learning Models on Mathematical Creative Thinking Abilities Viewed from the Self-Directed Learning of SMK - Athikah, Athikah; Kamid, Kamid; Haryanto, Haryanto (Universitas Suryakancana, 2023)
Mathematical creativity is still lacking in Revany Indra Putra Vocational School in Jambi City when it comes to solving mathematical puzzles. The purpose of this study is to ascertain the following: 1. How students' mathematical creative thinking abilities are affected when Discovery Learning, Problem Based Learning, and Direct Instruction models are applied; 2. How students' mathematical abilities are affected when they self-directed learn; and 3. How students' mathematical creative thinking abilities are impacted when learning models are applied and self-directed learning occurs. With an experimental group and a control group, this study is quasi-experimental in nature. Using the Simple Random Sampling method, samples were drawn at random. Mathematical creative thinking ability test questions, self-directed learning questionnaires, and observation sheets for learning models are the tools employed. Two-way ANOVA analysis was used to assess the data from this study. First hypothesis findings were 0.017 <0.05, second hypothesis results were 0.019 <0.05, and third hypothesis results were 0.000 <0.05. The following conclusions can be drawn: 1. The use of Discovery Learning, Problem Based Learning, and Direct Instruction models has an impact on students' mathematical creative thinking abilities; 2. Learning independence has an impact on students' mathematical creative thinking abilities; and 3. There is an interaction between the use of model learning and students' self-directed learning with regard to their capacity for mathematical creativity.